ANALISIS PENCAHAYAAN LAMPU PENERANGAN JALAN UMUM (LPJU) PADA JALAN TOL SEMAYANG - Satrio, Yogi Waliy; Fahreza, Muhammad; Tarigan, Amani Darma (Power Elektronik : Jurnal Orang Elektro, 2024)
Several issues with public street lighting are often found and do not meet the Indonesian National Standard (SNI). Common problems include uneven spacing between streetlight poles, improper pole heights, poorly organized streetlight installations, and incorrect selection of lamp types and wattages according to the SNI standards. The lack of streetlights on busy road sections results in inefficient operation and discomfort for road users due to inadequate light intensity at the streetlight locations caused by various factors. To address these issues, solutions are needed to improve the existing situation, including energy-saving measures for public street lighting. Some necessary actions include replacing non-compliant streetlights and conducting evaluations by relevant authorities after installation works are completed. The existing condition of streetlights along the Semayang Toll Road shows an average illumination level produced by 150W SON-T lamps of 3.1 lux with light uniformity of 0.0, which does not comply with SNI 7391:2008. Simulation results using Dialux 4.13 software indicate that the average illumination level produced by Philips LED luminaires of 150W is 11 lux with a light uniformity of 0.106 lux, meeting SNI 7391:2008 requirements. Similarly, for Philips LED luminaires of 120W, the average illumination level is 11 lux with a light uniformity of 0.114 lux, thus meeting the standards. Based on the simulation results using Dialux 4.13 software, the use of 120W LED lamps for public street lighting on the Semayang Toll Road can lead to a 20% reduction in electricity consumption.